IMPLEMENTASI PERMENSESNEG NO 14 TAHUN 2012 TENTANG STANDAR PELAYANAN KESEHATAN DASAR PADA BAGIAN PELAYANAN KESEHATAN, BIRO UMUM, KEMENTERIAN SEKRETARIAT NEGARA DI JAKARTA - Indah Wahyu Maesarini; Yuni Subiyanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
The government of Indonesia guarantees equal rights and status of every citizen in obtaining services. However, in reality, various problems still occurredsuch as complicated service procedures andthe length of time and infrastructure services. Ineffective and inefficient bureaucracy services hamper health service processes to officers/employees and their families in the Ministry of the State Secretariat. Therefore, the Minister of State Secretary issued the Ministerial Decree of the State Secretary No. 14 year 2012 regarding Service Standard of Working Unit in the Ministry of the State Secretariat. The purpose of this study is to find out how the Ministerial Decree of the State Secretary No. 14 year 2012 is implemented, especially Basic Health Service Standard in the Division of Health Services, General Bureau, The Public Ministry of the State Secretariat. This research used a qualitative descriptive approach to describe the implementation of Basic Health Service Standard in the Division of Health Services, General Bureau, The Ministry of the State Secretariat. The study found that the Division of Health Services, General Bureau, General Affairs, the Ministry of the State Secretariat has not implemented all the policies of basic health service standard. However, in most cases it does not hamper the implementation of health services to the officers/employees and their employees in The Ministry of the State Secretariat.